PENGARUH JENIS AIR MINUM TERHADAP PERFORMAN PERTUMBUHAN PUYUH (Coturnix coturnix japonica): Ria Anjalani1), Satrio Wibowo1) , Araino Jagauku2) , (Agrienvi: Jurnal Ilmu Pertanian, 2020)
This study was conducted to determine the effect of various types of drinking water on growingperformance of quail. The study used a completely randomized design (CRD) with 4 treatments and 5replications. Each replication consisted of 3 quails. The treatments were P1 (groundwater), P2 (Water produceby the regional drinking water company), P3 (Local commercial drinking water), and P4 (Branded commercialdrinking water). The observed variables were water intake, feed intake, body weight gain, final body weight andfeed convertion ratio of quails. Data were analyzed with analysis of variance. The study showed various type ofdrinking water did not significantly affect on growing performance of quails on 21-56 age in all variables(P>0.05). It was concluded that the different types of drinking water did not have potential to affect on growingperformance of quails.Key words :growing performance, various types of drinking water, quail